The impact of career calling on higher vocational nursing students’ learning engagement: The mediating roles of career adaptability and career commitment - Chen, Jingyuan; Zhang, Xiaoxia (Frontiers in Psychology, 2023)
Learning engagement is an important predictor of academic success and a key indicator of educational quality. It has therefore attracted considerable research interest, with previous studies exploring how to enhance engagement via pedagogical approaches, strategies, and content, as well as through teacher-student interaction. However, the relationship between individual learners’ internal mechanisms and learning engagement has yet to be investigated in depth. Accordingly, the present study explored the direct effects of career calling on higher vocational nursing students’ learning engagement and the mediating roles of career adaptability and career commitment via a parallel mediation model. Data were collected from 388 nursing students at two higher vocational colleges in China and the hypotheses were tested using correlation and regression analyses. The results showed that career calling imparted a significant positive effect on the nursing students’ engagement in learning, with career adaptability and career commitment mediating this relationship. These findings highlight the importance of promoting learning engagement among nursing students and the need to carefully design instructional activities for the healthcare profession.